2017
DOI: 10.1016/j.prosdent.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whitening dentifrice on yttria-stabilized tetragonal zirconia polycrystal surfaces after simulating brushing

Abstract: Brushing Y-TZP with conventional dentifrice increased roughness, while brushing with whitening dentifrice reduced roughness. Neither dentifrice changed the crystallographic phases after brushing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
5
0
2
Order By: Relevance
“…The roughness of zirconia is crucial because it increases the contact area with moisture, which could result in low-temperature degradation [33,34]. In addition, a whitening dentifrice reduced the surface roughness of the polished zirconia surface, which corroborated the results from Pinelli et al [12]. The high RDA of a whitening dentifrice was considered to exert a polishing effect on the zirconia surface.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The roughness of zirconia is crucial because it increases the contact area with moisture, which could result in low-temperature degradation [33,34]. In addition, a whitening dentifrice reduced the surface roughness of the polished zirconia surface, which corroborated the results from Pinelli et al [12]. The high RDA of a whitening dentifrice was considered to exert a polishing effect on the zirconia surface.…”
Section: Discussionsupporting
confidence: 62%
“…The toothbrushing procedure involves applying a mechanical force to the tooth surface over a prolonged period [10]. In addition, various dentifrices have been developed for use with toothbrushes, and chemical components and abrasives of dentifrices can chemically and physically affect the surface of brushed teeth [11,12]. The high fluoride concentration in a dentifrice has been reported to diminish the properties of dental ceramics [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(14) Even with the higher hardness zirconia blocks, the results found in this study showed that all zirconia specimens brushed with dentifrice subjected to more roughness and surface topography that is agree with some investigators. (39)(40)(41) That is may be attributed to its low temperature degradation that occurs in moist environments. (40,41) Another explanation is probably related to the influence of pH variations and the concentration of fluoride on the zirconia's susceptibility to degradation.…”
Section: Discussionmentioning
confidence: 99%